Effects of feeding zooplankton, Moina macrocopa (Straus, 1820) on the growth of Nile tilapia Oreochromis niloticus L. - Islam, MR; Hassan, MR; Begum, M; Punom, NJ; Begum, MK; Sultana, N; Rahman, MS (Bangladesh Journal of Scientific and Industrial Research, 2017)
Studies were carried out on the growth performance of Tilapia fry, Oreochromis niloticus cultured with zooplankton, Moina macrocopa in comparison to commercial feed. Three types of feed were used in three treatments where treatment-1 was fed with handmade feed (control), treatment-2 with commercial feed and treatment-3 with live zooplankton M. macrocopa. Thirty fry were stocked in each 60 L aquarium for a rearing period of 56 days. The fishes were fed twice a day at 90-400 Moina/individual fish for first 20 days, then 500-850 Moina/individual fish for 15 days and 900-1250 Moina/individual fish for remaining days. Sampling was done at 14 days interval. The growth performance of M. macrocopa was higher in the treatment fed with Spirulina which was 6350 individuals/ L of water and in the treatment fed with yeast it was 5100 individuals/L of water at 12th days. The study showed that condition factor of tilapia fry found in treatment-3 fed with M. macrocopa was comparatively higher (2.18±0.09) than that of treatment-2 fed with commercial feed (1.86±0.13) at a 56-day culture period. Average daily gain was significantly higher in the treatment-3 fed with M. macrocopa (0.13±0.01) than those of treatment-1 (0.06±0.01) and treatment-2 (0.08±0.01). The best value of feed conversion ratio and specific growth rate was found in treatment-3 fed with M. macrocopa than commercial feed and handmade feed. Protein content was significantly higher (15.91%) in treatment-3 than those of treatment-1 (10.96%) and treatment-2 (11.88%). The findings of this study suggest that growth parameters and body composition of Nile Tilapia was better in treatment-3 fed with M. macrocopa. Bangladesh J. Sci. Ind. Res. 52(2), 81-88, 2017